Acquiring combat capability through innovative uses of public private partnerships - Buchanan, Steven M.; Cabell, Jayson W.; McCrary, Daniel C. (Monterey, California. Naval Postgraduate School, 2006)
Acquisition research (Graduate School of Business & Public Policy) This research examined the federal government's historical use of public-private partnerships (PPPs) to determine whether or not Energy Savings Performance Contracts (ESPC) should be applied to mobile assets. Third party financing of capital improvements through PPPs has resulted in reduced energy consumption and savings to tax-payers. For example, to modernize existing facilities, the government has used private corporations, such as Hannon-Armstrong, LLC, to overcome shortfalls in appropriated funds. Third party financing and ESPCs present viable solutions to modernizing and reducing the energy consumption of the government's mobile assets. The first part of this research examines Hannon Armstrong's fee for service contract solution to funding the vital fiber-optic link near the Arctic Circle. The second part explores the history of the Energy Saving Performance Contracts (ESPCs), which have helped reduce energy consumption throughout the federal government. Historically, this program has only been used for fixed assets. There is little debate over the success of these contracts in reducing energy consumption. The authors conclude that applying Energy Savings Performance Contracts to mobile assets could further reduce the energy consumption of the Department of Defense (DoD) and save tax-payers millions of dollars. Approved for public release; distribution is unlimited.